1997
DOI: 10.1152/ajpendo.1997.273.1.e156
|View full text |Cite
|
Sign up to set email alerts
|

Water deprivation upregulates ANG II AT1 binding and mRNA in rat subfornical organ and anterior pituitary

Abstract: We studied angiotensin II (ANG II) receptor subtype expression in selected brain nuclei and pituitary gland after water deprivation by in vitro receptor autoradiography using 125I-labeled [Sar1]ANG II and by in situ hybridization using 35S-labeled AT1A, AT1B, and AT2 receptor-specific riboprobes. In control rats we found binding to AT1 receptors in the subfornical organ, paraventricular nucleus, median eminence, and anterior pituitary; AT1A mRNA expression in the subfornical organ and paraventricular nucleus; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…Studies in which in situ hybridization and polymerase chain reaction methods were used for the localization and quantification of the mRNA for the AT1-receptor subtypes showed that AT1b receptors were of a lower density and were expressed in brain, testes, adrenal, kidney, and pituitary. 4,7,8,15,18,36 In the rat brain, there is strong evidence for the presence of AT1b mRNA in AP and more controversy regarding its localization in SFO. 4,15,18 The question is whether the mRNA is directly translatable into receptor protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies in which in situ hybridization and polymerase chain reaction methods were used for the localization and quantification of the mRNA for the AT1-receptor subtypes showed that AT1b receptors were of a lower density and were expressed in brain, testes, adrenal, kidney, and pituitary. 4,7,8,15,18,36 In the rat brain, there is strong evidence for the presence of AT1b mRNA in AP and more controversy regarding its localization in SFO. 4,15,18 The question is whether the mRNA is directly translatable into receptor protein.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the receptor subtypes, 0. 4 14 C to 125 I-Ang II in fmol/mg protein. 26 Different exposure times were used to obtain accurate readings for high, moderate, and low densities of binding according to the linear range of the film.…”
Section: Receptor Autoradiographymentioning
confidence: 99%
See 2 more Smart Citations
“…Water deprivation leads to an up-regulation of ANG II receptor binding and AT 1A receptor gene expression (5,53) as well as an increase in steady state AoGen mRNA levels in the rat SFO (5). The simultaneous increase in TTF-1 mRNA and protein and AoGen mRNA observed in the SFO after 2 days of water deprivation suggests that dehydration up-regulates AoGen synthesis in the SFO via activation of TTF-1 production.…”
Section: Ttf-1 Regulates Ang Transcription In Subfornical Organmentioning
confidence: 99%